Analysis and comparison of computer programs to analyze the irradiation performance of Uranium Molybdenum monolithic fuel plates and Uranium dioxide cylindrical fuel rods in power reactors. - André Luiz Candido da Silva; Antonio Teixeira e Silva (Brazilian Journal of Radiation Sciences, 2021)
The aim of this work is to present a comparative analysis in terms of the irradiation performance of cylindrical uranium dioxide fuel rods and monolithic uranium molybdenum fuel plates in pressurized light water reactors.